Behavior of precast composite columns under axial and transverse forces - Ercan, Emre; Hökelekli, Emin; Arisoy, Bengi; Hökelekli, Emin (Elsevier, 2021)
In this study, the effect of the steel core orientation to combined stresses behavior of a concrete encased steel (CES) composite column was studied. The various sectional configurations were used to define contributions to capacity under compression and flexural loading. CES composite sections were generally designed as column to resist axial compression and biaxial bending. This study would provide better understanding in case the section should carry flexural bending beside axial compression. The samples were tested under constant axial and repeated transverse forces, and a finite element analysis (FEA) model was developed to express flexural behavior of the composite column and to verify the experimental study. A total of four concrete encased steel composite columns with differently oriented I-shaped and circular tube steel sections and a reinforced concrete column were tested. Behavior of the columns were evaluated regarding failure modes, load versus displacement relationships and ultimate strength. Experimental results indicated that the specimen with steel section oriented regarding tension region exhibited better flexural response.
Keywords: Concrete Encased Steel Composite Columns; Axial And Flexural Loading; Flexural Stiffness